Study on the thermal behavior of the complexes of the type [PdX2(tdmPz)] (X = Cl-, Br-, I-, SCN-) - Rocha, Fillipe V. [UNESP]; Barra, Carolina V. [UNESP]; Franchi, Silmar J. S. [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Mauro, Antonio Eduardo [UNESP]; Frem, Regina Célia Galvão [UNESP] (Springer, 2011)
Four new mononuclear Pd(II) complexes of the type [PdX2(tdmPz)] {X = Cl- (1); Br- (2); I- (3); SCN- (4); tdmPz = 1-thiocarbamoyl-3,5-dimethylpyrazole} have been synthesized and characterized by elemental analysis, IR spectroscopy, H-1 and C-13{H-1}-NMR experiments. The thermal behavior of the complexes 1-4 has been investigated by means of thermogravimetry (TG) and differential thermal analysis (DTA). From the initial decomposition temperatures, the thermal stability of the complexes can be ordered in the sequence: 3 < 4 a parts per thousand 2 < 1. The final products of the thermal decompositions were characterized as metallic palladium by X-ray powder diffraction.
Keywords: Pd(II) complexes; 1-thiocarbamoyl-3,5-dimethylpyrazole; TG and DTA